Innovating community engagement: the role of micro-influencers in promoting sustainable behaviors among Malaysian millennials - Shafie, Latisha Asmaak; Rosaidi, Nor Alifah; Mohd Radzi, Nor Azira; Ku Akil, Ku Azlina; Razali, Razlina; Lew, Ya Ling (Universiti Teknologi MARA, Kedah, 2024)
Social Influencers as environmental leaders utilise social media platforms to enhance community engagement in advocating sustainability. This study explores the underexplored role of microinfluencers in fostering pro-environmental behaviors among Malaysian youths and innovating community engagement by employing a qualitative approach in conducting semi-structured interviews with five micro-influencers. Our findings indicate the critical role of micro-influencers in raising awareness and actively engaging communities in the adoption of sustainable practices. The findings reveal three key themes: leadership qualities, pro-environmental behaviors, and persuasive narrative strategies. Through the innovative use of social media, these influencers overcome linguistic and geographical barriers, fostering enhanced community engagement in the pursuit of environmental stewardship. However, the sample size of five micro-influencers may limit the generalizability of the findings, as it may not fully represent the diverse range of microinfluencers. The result of this research can be used as recommendations for organisations, nongovernmental organisations and governmental bodies can leverage the insights from this study to strategically engage micro-influencers in environmental campaigns, recognizing their unique ability to reach and resonate with specific communities, particularly Malaysian youths. This study offers a novel perspective on digital environmental leadership by uncovering the unique role of microinfluencers in fostering community engagement and cultivating a culture of sustainability. It provides original insights into how these emerging leaders not only inspire but also empower communities to take meaningful action towards environmental preservation. The study highlights the underexamined potential of micro-influencers in exceeding traditional barriers to community engagement, offering valuable implications for future strategies in environmental advocacy.